2017
DOI: 10.5978/islsm.17-or-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of marginal microleakage of flowable composite restorations in primary canine teeth prepared with high-speed diamond bur, Er:YAG laser and Er,Cr:YSGG laser

Abstract: Use of Er:YAG and Er,Cr:YSGG lasers can decrease microleakage to the level of bur preparation. Bur and laser cavity preparations are not significantly different in terms of microleakage at the enamel or dentin margins. Thus, considering the advantages of laser, it may serve as a suitable alternative to bur preparation in pediatric dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
0
13
0
5
Order By: Relevance
“…In the present study, the micro-leakage test was performed after all teeth were thermos-cycled for 500 cycles from 5 °C to 55 °C with 30 s dwell time, 20 s transfer time, as this would correspond to six months' clinical use and therefore would give more practical results on the intraoral performance of the restoration. (29) The result of this study showed that fissure pretreatment with either SDF or NSF presented better results with no dye penetration than FS without pre-treatment: 66.66%, 73.33%% and 46.66% respectively, however, this difference didn't reach the level of significance. This finding indicated that the sealing ability of FS was not affected when enamel was pretreated with either SDF or NSF.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the present study, the micro-leakage test was performed after all teeth were thermos-cycled for 500 cycles from 5 °C to 55 °C with 30 s dwell time, 20 s transfer time, as this would correspond to six months' clinical use and therefore would give more practical results on the intraoral performance of the restoration. (29) The result of this study showed that fissure pretreatment with either SDF or NSF presented better results with no dye penetration than FS without pre-treatment: 66.66%, 73.33%% and 46.66% respectively, however, this difference didn't reach the level of significance. This finding indicated that the sealing ability of FS was not affected when enamel was pretreated with either SDF or NSF.…”
Section: Discussionmentioning
confidence: 60%
“…(28) Two layers of nail varnish was then applied over the teeth leaving only one mm free around the occlusal sealant border. (29) The occlusal surface of each tooth was then immersed in 1% methylene blue dye solution (pH=7) at 37 º C for 24 hours and stored in incubator, this permitted the dye penetration into the existing voids between the tooth substance and the restorative material. (30) The teeth were then washed under tap water and were sectioned mesio-distally in the center of the fissure with low speed water-cooled diamond saw giving 30 specimens in each group.…”
Section: Groupingmentioning
confidence: 99%
“…After screening the titles and abstracts, the full texts of 21 articles were obtained for more detailed data. Finally, 13 studies were included, 11 of which were selected for meta-analysis [ 4 – 9 , 12 , 15 18 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The member of erbium laser family, Erbium, Chromium: Yttrium Scandium Gallium Garnet (Er,Cr:YSGG) has gained the approval for caries removal and cavity preparation by Food and Drug Administration(FDA) [ 3 ]. Compared with traditional burs, Er,Cr:YSGG laser does not contact the tooth directly and has less vibration, noise, pressure, and thermal damage during cavity preparation [ 4 ]. Moreover, previous studies have reported a significant alteration in surface topography of the cavity after laser preparation, which might improve adhesion and the restorative procedure [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literatura mostra que esse efeito térmico causado por esse sistema, resulta em uma superfície com uma morfologia significativamente diferente da obtida pela broca. Esta morfologia é capaz de influenciar a resistência ácida das margens das cavidades preparadas com os lasers de érbio no esmalte e prevenir lesões em parede de restauração, as camadas de lesões de cárie secundárias, em modelos in vitro ( Eick et al, 2017, Malekafzali et al, 2017. Considerando os benefícios mencionados acima, apesar de ainda representar uma tecnologia que exige um investimento alto e necessidade de um conhecimento especializado para seu uso, esse tipo de sistema promove vantagens clínicas relevantes.…”
Section: Discussionunclassified